2018
DOI: 10.1002/jcb.26881
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein inhibits breast cancer growth via activating a novel isoform of the long noncoding RNA PAX8‐AS1‐N

Abstract: Baicalein, a natural flavonoid, has fascinating anti-cancer properties in breast cancer. Long noncoding RNAs (lncRNAs), a class of transcripts with no protein-coding potential, also exhibit critical roles in breast cancer. However, the molecular mechanisms mediating the anti-cancer properties of baicalein and whether lncRNAs are involved in the anti-cancer effects are still unclear. In this study, we identified a novel isoform of lncRNA PAX8-AS1 (PAX8-AS1-N), which is activated by baicalein in a dose- and time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 59 publications
(125 reference statements)
2
21
0
Order By: Relevance
“…An up-regulation in NKILA expression by IDET may suppress IκB phosphorylation and NF-κB activation. Similar to these observations, the anti-invasive activities of TGF-β 47 and anti-carcinogenic activities of baicalein 48 are mediated through NKILA.…”
Section: Discussionsupporting
confidence: 70%
“…An up-regulation in NKILA expression by IDET may suppress IκB phosphorylation and NF-κB activation. Similar to these observations, the anti-invasive activities of TGF-β 47 and anti-carcinogenic activities of baicalein 48 are mediated through NKILA.…”
Section: Discussionsupporting
confidence: 70%
“…Compared with small molecule chemical drugs, natural products have higher therapeutic safety. They also could affect the expression level of lncRNAs, which is crucial for tumor progression (50)(51)(52)(53). In this research, we confirmed that fucoidan could effectively inhibit the progression of HCC.…”
Section: Introductionsupporting
confidence: 68%
“…4 Baicalein has important pharmacological activities, such as anti-tumorous, anti-inflammatory, antiviral and antioxidative effects. 5 Issued reports have found the inhibitory effects of baicalein on various human cancers, including non-small cell lung cancer, 6 hepatocellular carcinoma, 7 breast cancer, 8 thyroid cancer, 9 and so on. Regarding the functional mechanisms of anticancer baicalein, it is mainly because of its inhibition on cell cycle progression by regulating cyclins, promotion of apoptosis by activating caspase-3/9, and the activity repression of mitogen-activated protein kinase (MAPK), protein kinase B (AKT) or mammalian target of rapamycin (mTOR).…”
Section: Introductionmentioning
confidence: 99%